Socio-Demographic Characteristics and Hysteroscopic Findings among Women with Unsafe Abortion in South-South Nigeria - Edet, Ekpo Effiong; Efiok, Efiok Eyo; Njoku, Amarachukwu Nnaemezie; Abeshi, Sylvester Etenikang; Ezukwa, Ezukwa Omoronyia; Nzeadibe, Jessica Tochukwu (International Journal of Innovative Research in Medical Science, 2021)
Background: Abortion is unsafe when it is carried out either by a person lacking the necessary skills or in an environment that does not conform to minimal standard, or both. It is complicated by intrauterine adhesions and secondary infertility. Objectives: To determine the socio-demographic features and hysteroscopic findings of women that had unsafe abortion in Calabar, Nigeria. Methodology: It was a cross-sectional study of 66 women in reproductive age, presenting in gynaecological clinic who consented to hysteroscopy between August 2019 to September 2020. A structured questionnaire was used to obtain sociodemographic data and hysteroscopy was done. Results: There was no significant difference in socio-demographic characteristics between women that have undergone unsafe abortion and those that have not. Cervical stenosis (76.9%) (p = 0.005) and intrauterine adhesions (68.3%) (p = 0.005) were significantly higher in women who had unsafe abortion. The odd ratios of cervical stenosis and intrauterine adhesions for 1 and ≥2 unsafe abortions were not significant. Conclusion: Cervical stenosis and intrauterine adhesions were significant complications of unsafe abortion in our environment. Multiple unsafe abortions do not confer significant higher risk of cervical stenosis or intrauterine adhesions.